Effect of Short-term Exercise on Appetite, Energy Intake and Energy-regulating Hormones - Ebrahimi, Mohsen (Mashhad University of Medical Sciences, 2013)
Objective(s) : The purpose of this study was to investigate effects of short-term aerobic exercise on energy intake, appetite and energy-regulating hormones in free-living men and women. Materials and Methods: Sixteen (eight men, eight women) sedentary young normal weight subjects participated in two experimental conditions with two days apart: five days control with no exercise, and five days exercise (55% MHRR for 45 min/day). Subjects recorded dietary intake using a food diary and self-weighed intake during each five days. Appetite questionnaire (visual analogue scale) was completed each morning in the fasted state. Blood samples were taken in the morning on the 6th day in fasting status after control and exercise conditions. Results: No significant changes were found in absolute energy intake, appetite rate and level of acylated ghrelin and leptin between conditions in both sexes. In women, insulin concentration decreased significantly after exercise. Relative energy intake was significantly lower after exercise in men. On average, women compensated for about 23% of the exercise-induced energy deficit but men did not (-10%). Conclusion: Our findings show that low-intensity exercise for five consecutive days cannot create a negative energy balance in women. It seems that women are more resistant to exercise-induced energy deficit.